Mechanisms of innate immune activation by gluten peptide p31-43 in mice - Araya, Romina Elizabeth (2016)
Celiac disease (CD) is an immune-mediated enteropathy triggered by gluten in genetically susceptible individuals. Innate immunity contributes to the pathogenesis of CD, but the mechanisms remain poorly understood. Although previous in vitro work suggests that gliadin peptide p31-43 acts as an innate immune trigger, the underlying pathways are unclear and have not been explored in vivo. Here we show that intraluminal delivery of p31-43 induces morphological changes in the small intestinal mucosa of normal mice consistent with those seen in CD, including increased cell death and expression of inflammatory mediators. The effects of p31-43 were dependent on MyD88 and type I IFNs, but not Toll-like receptor 4 (TLR4), and were enhanced by coadministration of the TLR3 agonist polyinosinic:polycytidylic acid. Together, these results indicate that gliadin peptide p31-43 activates the innate immune pathways in vivo, such as IFN-dependent inflammation, relevant to CD. Our findings also suggest a common mechanism for the potential interaction between dietary gluten and viral infections in the pathogenesis of CD.